Strategi Pelestarian Peralatan dan Infrastruktur Pertambangan Minyak dari Masa Kolonial di Sangasanga Kalimantan Timur - Wasita (Jurnal Pendidikan dan Kebudayaan, 2016)
The study aimed to obtain a proper strategy in the preservation of colonial archaeological remains in Sangasanga with community involvement. Therefore, the method used was a descriptive analysis by providing a complete picture of archaeological data. The result shows that the most effective preservation is by involving local community. In this case, people are not merely engaged to work but a system is made which conducts utilization concept and has additional value to earn profit. Utilization of occupying the building (for example komplak) and earned income are through economic activities related to cultural heritage tour. Hopefully, involving local people in the conservation will be easily realized through the activities. Nevertheless, the system could not be allowed to work alone. There should be monitoring and evaluation in order to implement conservation habits become an attitude of life. The conclusion of this study is that the preservation action for oil company equipment and infrastructure in Sangasanga should promptly be done by conservation strategy with added values by involving the community.